Two new gladiatorial monuments from Amphipolis - Nigdelis, Pantelis; Tzelepidou, Anny (Tekmeria, 2017)
The paper publishes a) a new stele which bears a relief representing a gladiator in a shallow rectangular panel, twelve engraved crowns in the left and down sides, and an engraved palm branch b) a funeral inscription found in a grave at Amphipolis, whose gladiatorial nature is evident from stereotypic formulae.